1994
DOI: 10.3801/iafss.fss.4-539
|View full text |Cite
|
Sign up to set email alerts
|

A Model For Predicting Concentrations Of Carbon Monoxide In Building Fires

Abstract: Several experiments conducted to date suggest that yield of carbon monoxide is strongly affected by 'equivalence ratio'. So it seems worthwhile to develop an empirical model of CO yields as a function of equivalence ratio, and to use this model as the source term in fire models for the prediction of CO concentrations in building fires. In the preceding paper, we presented a theoretical model for predicting the yields of chemical species for propane fire.In this paper, we extend the model to generic fuel, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…When the rate of gasifying fuel is /g/s, the rates of generation of product species are as shown in Equations (2) through (7).…”
Section: Rate Of Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the rate of gasifying fuel is /g/s, the rates of generation of product species are as shown in Equations (2) through (7).…”
Section: Rate Of Generationmentioning
confidence: 99%
“…and Tanaka[2] ] obtained empirical values or equations for parameters related to mole ratios of CO, C, H 20, H 2 , and unburnt fuel from Beyler's experimental…”
mentioning
confidence: 99%
“…where y O ðf; TÞ is the oxygen consumption as 1 kg fuel is vaporized. y i ðf; TÞ is the yield (kg) of product i per kg fuel as the equivalence ratio is f and temperature is T. The mass fraction of the products are in this study calculated by using Equations (7)- (10) and (14). These equations do not depend on the fuel mass fraction Y f : Therefore, the heat released from the fire can be represented by a heat source while the combustion process is ignored.…”
Section: Calculation Of Productsmentioning
confidence: 99%
“…The generation of CO in burning of some fuel materials is well correlated to the equivalence ratio concept for both the hood experiments and the reduced room fires. Based on this concept, several zone models have been developed to predict the average concentration of CO in the upper layer of both reduced-scale and full-scale compartments [9,10]. However, a possible shortcoming of this technique, when applied to zone models, is that the technique predicts similar upper layer CO concentrations for both these two fire scenarios when the ventilation conditions (GERs) are similar.…”
mentioning
confidence: 99%
“…The third approach recommends using values derived from experiments. [3], [9], [10] Two types of studies have been suggested as sources for the required values. The 6rst is based on experiments in which flame gases are quenched in a hood placed above fires burning in an open laboratory.…”
Section: Current Approaches For Co Estimationmentioning
confidence: 99%